Structure Prediction and Potential Inhibitors Docking of Enterovirus 2C Proteins - Li, Daoqun; Zhang, Leiliang (Frontiers in Microbiology, 2022)
Human enteroviruses infections are mostly asymptomatic and occasionally could be severe and life-threatening. The conserved nonstructural 2C from enteroviruses protein is a promising target in antiviral therapies against human enteroviruses. Understanding of 2C-drugs interactions is crucial for developing potential antiviral agents. While functions of enterovirus 2C proteins have been widely studied, three-dimensional structure information of 2C is limited. In current study, the structures of 2C proteins from 20 enteroviruses were simulated and reconstructed using I-TASSER programs. Subsequent docking studies of the known 22 antiviral inhibitors for 2C proteins were performed to uncover the inhibitor-binding characteristics of 2C. Among the potential inhibitors, the compound hydantoin exhibited the highest broad spectrum antiviral activities with binding to 2C protein. The anti-enteroviral activity of GuaHCL, compound 19b, R523062, compound 12a, compound 12b, quinoline analogs 12a, compound 19d, N6-benzyladenosine, dibucaine derivatives 6i, TBZE-029, fluoxetine analogues 2b, dibucaine, HBB, metrifudil, pirlindole, MRL-1237, quinoline analogs 10a, zuclopenthixol, fluoxetine, fluoxetine HCl and quinoline analogs 12c showed a trend of gradual decrease. In addition, the free energy with 22 compounds binding to EV 2C ranged from -0.35 kcal/mol to -88.18 kcal/mol. Our in silico studies will provide important information for the development of pan-enterovirus antiviral agents based on 2C.